Quantitative rescattering theory of high-order harmonic generation for polyatomic molecules - Le, Anh-Thu; Lucchese, R. R.; Lin, C. D. (My University, 2013)
We report applications of the quantitative rescattering theory (QRS) for calculation of high-order-harmonic generation (HHG) from polyatomic molecules in ultrashort linearly polarized intense laser pulses, using the example of the CCl4 molecule. In particular, we present a detailed analysis and a treatment for the phase of the electron returning wave packet, which recollides with the parent molecular ion to emit high-energy photons. Our results show that Cooper-type minimum structures in the molecular photoionization cross section lead to quite distinguishable minima in the HHG spectra, even for unaligned polyatomic molecules.